Original paperDirect transcatheter aortic valve implantation – one-year outcome of a case control study - Kochman, Janusz; Kołtowski, Łukasz; Huczek, Zenon; Scisło, Piotr; Bakoń, Leopold; Wilimski, Radosław; Rymuza, Bartosz; Opolski, Grzegorz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Introduction : Transaortic valve implantation (TAVI) has a well-established position in the treatment of high-risk and inoperable patients with severe aortic stenosis (AS). The TAVI protocol requires a pre-dilatation for native valve preparation. Aim : To assess the safety and feasibility of TAVI without pre-dilatation and to compare it with the procedure with pre-dilatation. Material and methods: Out of 101 TAVI patients, in 10 the procedure was performed without balloon predilatation, and 8 patients were included in the analysis. The procedural, echocardiographic, and clinical outcomes were compared with a case control matched cohort (1 : 2 ratio). A 12-month follow-up was done in all cases. Results: The procedure was successfully completed in all patients in the study group (SG), but there was one procedural failure in the control group (CG). All patients received a CoreValve (Medtronic) bioprosthesis. There was a significant immediate decrease in transvalvular gradients (TG) in both study arms after the procedure (SG: mean TG: from 46.0 ±14.0 mm Hg to 10.0 ±4.8 mm Hg, p < 0.001; CG: mean TG: from 55.9 ±12.0 mm Hg to 9.9 ±2.9 mm Hg, p < 0.001). A marked increase in the effective orifice areas was observed in both cohorts (SG: 1.63 ±0.13 cm 2 and CG: 1.67 ±0.25 cm 2 , p = 0.75). The periprocedural complication rate was equally distributed in both arms. The 12-month all-cause mortality was 12.5% in both groups. Conclusions : The direct TAVI approach seams to be safe and feasible. The clinical and echocardiographic results are not different from those achieved in patients treated with standard TAVI protocol with pre-dilatation.